Decline in the performance of silicon solar cell parameters with the Ambient temperature in Baghdad (Journal of the College of Basic Education, 2023)
In this paper, the effect of Baghdad climate ambient temperature dependence (indoor and outdoor) of the performance of solar cell in the temperatures range (5 oC –70 oC) had been studied. The solar cell performance is determined by its main important parameters, short circuit current (Isc), open circuit voltage (Voc), fill factor (F.F) and efficiency (ηm). The experimental results of the parameters of silicon solar cell showed that the conversion efficiency was decline when the temperature raised from optimal temperature.